Simulation of atherosclerotic plaque growth using computational biomechanics and patient-specific data - Dimitrios S. Pleouras; Antonis I. Sakellarios; Panagiota Tsompou; Vassiliki Kigka; Savvas Kyriakidis; Silvia Rocchiccioli; Danilo Neglia; Juhani Knuuti; Gualtiero Pelosi; Lampros K. Michalis; Dimitrios I. Fotiadis (NATURE RESEARCH, 2025)
Atherosclerosis is the one of the major causes of mortality worldwide, urging the need for prevention strategies. In this work, a novel computational model is developed, which is used for simulation of plaque growth to 94 realistic 3D reconstructed coronary arteries. This model considers several factors of the atherosclerotic process even mechanical factors such as the effect of endothelial shear stress, responsible for the initiation of atherosclerosis, and biological factors such as the accumulation of low and high density lipoproteins (LDL and HDL), monocytes, macrophages, cytokines, nitric oxide and formation of foams cells or proliferation of contractile and synthetic smooth muscle cells (SMCs). The model is validated using the serial imaging of CTCA comparing the simulated geometries with the real follow-up arteries. Additionally, we examine the predictive capability of the model to identify regions prone of disease progression. The results presented good correlation between the simulated lumen area (P<0.0001), plaque area (P<0.0001) and plaque burden (P<0.0001) with the realistic ones. Finally, disease progression is achieved with 80% accuracy with many of the computational results being independent predictors.